Runoff variation and its attribution analysis in the typical basin of Loess Plateau at multiple temporal and spatial scales - Kaixin Jiang; Shuhong Mo; Mingkang Chen; Kunxia Yu; Jingyu Lyu; Peng Li; Zhanbin Li (Journal of Hydrology: Regional Studies)
Study region: Dali River Basin, a typical basin on the Loess Plateau (LP) in China Study focus: The LP has undergone extensive ecological management in recent decades, significantly altering runoff in the region. For more scientific management of basins, it is useful to study runoff variations at multiple scales quantitatively. Dali River Basin (DRB) was used as the model basin. The impacts of climate change (CC) and human activity (HA) were quantitatively analyzed based on the features of runoff changes at multiple scales using observed hydrological data from to 1960–2020. The characteristics of potential factors influencing HA were further analyzed. New hydrological insight for the region: The study showed that basin runoff was mainly concentrated during May-October. Spatially, most of the runoff originated from the middle and lower reaches, with little change in the upper reaches. Both CC and HA affected runoff variation, but their effects shifted from upstream to downstream. Apart from the upper reaches, HA was dominant in summer and autumn, whereas CC was dominant in spring and winter. Changes in runoff might be caused by temporal and spatial differences in HA, such as converting cultivated land into forests and grasslands, increasing NDVI, and constructing dams. This analysis of runoff variations at multiple temporal and spatial scales in a representative basin provides a reliable reference for the ecological management of the LP.